KAJIAN KEMANTAPAN AGREGAT TANAH PADA PEMBERIAN BEBERAPA JENIS BAHAN ORGANIK DI PERKEBUNAN KOPI ROBUSTA - Budy Satya Utomo; Yulia Nuraini; W Widianto (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2015)
Forest conversion for plantation and the continuous fertilizer usage without organic materials has potentials to produce soil damage with the soil compaction. One of efforts to improve sustainable land productivity is by applying organic materials. The use of organic materials of vermicompost, fruit peel fertilizer, and cow manure in long term is expected to be able to improve the physical properties of soil at the robusta coffee plantation (Coffea canephoraÂ Pierre). The research was conducted at robusta coffee plantation of PT Perkebunan Nusantara XII (Persero), Bangelan Village, Wonosari District, Malang Regency. The research used factorial random design of nested pattern with 2 factors: (1) organic material treatment (control, vermicompost, coffee fruit peel fertilizer, and cow manure),Â (2) the soil depth level (0-10 cm, 10-20 cm, and 20-30 cm. The results showed that application of vermicompos improved higher organic matter than the application of coffee peel fertilizer, cow manure in depth of 0-10 cm. The application of various organic materials did not improve the organic materials of soil in depth of 10-20 and 20-30 cm. The application of vermicompost, coffee peel fertilizer and cow manure improved aggregate stability than without the application of organic material (NPK). Organic materials had a positive relation with soil aggregate stability in depth of 0-10 cm (r = 61%), so the higher organic material content, the higher soil aggregate stability, while in depth of 10-20 cm and 20-30 cm there was no significant relationship